(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: A review of studies conducted on sexuality in India has revealed that premarital sex in youth is prevalent in 0-10 percent of women and 15-30 percent men and it is on rise. The young people indulge in risky behavior pattern such as infrequent or irregular contraceptive use. Youth is facing a significant risk of sexual health and lack in making informed sexual choice. The objective of this study is to explore the HIV/AIDS related knowledge and sexual attitudes held by young students from Laddakh Methodology: Systematic sampling was used to collect data from 100 Laddakhi students living in Jammu in the age range 18-29 years. The mean age of the sample was 22.28. Sexual Attitude Scale and HIV Related Knowledge Questionnaire were applied in this study. Results: The results of test indicate significant gender differences in sexual attitudes. The male Laddakhi students held more favorable attitude towards pre marital sex, polygamy and pornography than their female counterparts. In comparison to male participants, the young female participants reflected favorable attitude towards establishing same sex relationships. The participants in the study also hold misconceptions about HIV/AIDS. Conclusions: In addition to low level of awareness on HIV/AIDS, holding favorable sexual attitudes might result in involvement in risky sexual behavior. Organizing awareness campaigns at school level to focus the youth might be useful in curbing the potential involvement of young students in risky sexual behavior. SAARC J TUBER LUNG DIS HIV/AIDS, 2015; 12(1), Page: 14-19